Criminal justice in north-west New South Wales - Cunneen, Chris, 1953-; Robb, Tom.; New South Wales. Bureau of Crime Statistics and Research (Sydney : N.S.W. Bureau of Crime Statistics and Research, 1987)
Report on claims of law and order crisis in 1985; demographic, economic and social background; analysis of crime statistics, court reports; juvenile crime; police /community relations; focus on Dubbo, Brewarrina, Bourke , Walgett, Wellington; discrimination.
Bibliography: p. 223-229.
Keywords: Crime -- New South Wales; Aboriginal Australians -- New South Wales -- Social conditions; Juvenile delinquency -- New South Wales; Race relations - Racial discrimination - Courts; Race relations - Racism - Stereotyping; Law enforcement - Police conduct and attitudes; Law enforcement - Police-youth relations; Law enforcement - Criminal law and procedure; Crime and imprisonment statistics; Demography - Population mobility; Brewarrina (N NSW SH55-06); Walgett (N NSW SH55-11); North West New South Wales (NW NSW SH54, SH55, SI54); Bourke (N NSW SH55-10); Wellington (N NSW SI55-04); Murdi Paaki / Bourke (N NSW SH55-10); Northwest New South Wales (NW NSW SH54, SH55, SI54); Dubbo (N NSW SI55-04); Southwest New South Wales (SW NSW SI54, SI55)